Perceived coach-autonomy support, basic need satisfaction and the well- and ill-being of elite youth soccer players: A longitudinal investigation - Adie, J.; Duda, J.; Ntoumanis, Nikos (Elsevier BV, 2012)
Objectives: Drawing from the basic needs theory [BNT; Ryan, R. M., & Deci, E. L. (2002). An overview of self-determination theory. In E. L. Deci, & R. M. Ryan (Eds.), Handbook of self-determination research (pp. 3–33). Rochester, NY: University of Rochester Press], the major purpose of the present study was to test a hypothesized sequence of temporal relationships between perceptions of coach-autonomy support, basic need satisfaction and indices of well- and ill-being. A subsidiary aim was to ascertain the assumed mediational role of basic need satisfaction in explicating the perceived autonomy support and well-/ill-being relationships over time. Design: A field-based longitudinal design was employed. Methods: Participants (N = 54 males) from an elite youth soccer academy in the UK completed a multi-section questionnaire tapping the targeted variables on six occasions across two competitive seasons. Results: Multi-level regression analyses revealed that perceptions of coach-autonomy support positively predicted within-person changes and between-person mean differences in basic need satisfaction and well-being over time. Satisfaction scores for the needs for competence and relatedness were found to predict within-person changes in subjective vitality. These same needs partially mediated the coach-autonomy support–subjective vitality link over the two seasons. Conclusions: The findings partially support the tenets of BNT, and are discussed in terms of their practical application to participants involved in an elite youth sport setting.